High resolution reflection seismic profiling over the tjellefonna fault in the møre-trøndelag fault complex, Norway - Lundberg, E.; Juhlin, Christopher; Nasuti, A. (2012)
The Møre-Trøndelag Fault Complex (MTFC) is one of the most prominent fault zones of Norway, both onshore and offshore. In spite of its importance, very little is known of the deeper structure of the individual fault segments comprising the fault complex. Most seismic lines have been recorded offshore or focused on deeper structures. This paper presents results from two reflection seismic profiles, located on each side of the Tingvollfjord, acquired over the Tjellefonna fault in the southeastern part of the MTFC. Possible kilometer scale vertical offsets, reflecting large scale northwest-dipping normal faulting, separating the high topography to the southeast from lower topography to the northwest have been proposed for the Tjellefonna fault or the Baeverdalen lineament. In this study, however, the Tjellefonna fault is interpreted to dip approximately 50-60° towards the southeast to depths of at least 1.3 km. Travel-time modeling of reflections associated with the fault was used to establish the geometry of the fault structure at depth, while detailed analysis of first P-wave arrivals in shot gathers, together with resistivity profiles, were used to define the near surface geometry of the fault zone. A continuation of the structure on the northeastern side of the Tingvollfjord is suggested by correlation of an in strike direction P-S converted reflection (generated by a fracture zone) seen on the reflection data from that side of the Tingvollfjord. The reflection seismic data correlate well with resistivity profiles and recently published near surface geophysical data. A highly reflective package forming a gentle antiform structure was also identified on both seismic profiles. This structure could be related to the folded amphibolite lenses seen on the surface or possibly by an important boundary within the gneissic basement rocks of the Western Gneiss Region. The fold hinge line of the structure is parallel with the Tjellefonna fault trace suggesting that the folding and faulting may have been related. © Author(s) 2012.